The features of influence of educational socialization: factorial structure of basic directions - Bilodid, V. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
The article is discussed the features of the influence of educational socialization. It was presented the results of empirical research in the form factor model. It was determined two stages of educational socialization in higher education: the first mainly concerns the students of 1-2 courses, the second – the students of 3-6 courses. It was described the procedure and the methodology of the research. It was denoted the use of one-way ANOVA for independent samples to validate the hypotheses about the existence of certain differences between subjects: comparison of second year student of three different departments found no significant differences in the perception of learning environment, learning core competencies, characteristics of influence of the educational environment, indicators of psychological well-being, indicators causal orientations.Also, it was presented the method Student's t-test for independent samples to compare students from different courses that study at the same faculty: overall, between the second and fifth years of Historical Faculty, Faculty of Psychology and Military Institute found significant differences.It was used the Bartlett's Test of Sphericity to test the feasibility of using factor analysis to the selected data: the value of its significance indicates the validity and reliability of data for factorial method.It was defined and described the main factors on the specifics of influence of educational socialization. The resulting factors are revealing the structure of educational socialization in higher education, pointing to factors of its impact on students.
Keywords: educational socialization; factor model; training and education; competencies; university; direction of influence